The relationship between HPV testing attitudes and beliefs, knowledge, and vaccination attitudes: A cross-sectional study - Kucukkaya, Burcu; Sogut, Seda Cangol; Cangol, Eda (Wiley, 2024)
Objective: This study aims to examine the relationship between human papillomavirus (HPV) testing attitudes and beliefs, knowledge, and vaccination attitudes. Design: This study was a cross-sectional design. Sample: This study was conducted between March 15, 2024, and June 2, 2024, through social media platforms such as Facebook, Instagram, Twitter, and Telegram, by sharing on forum pages, and involved 674 women who volunteered to participate. Measurements: The research data were collected using the health belief model scale regarding HPV infection and vaccination (HBMS-HPVV) and the HPV Testing Attitudes and Beliefs Scale (HTABS), which were developed by the researchers through a literature review. Results: The average age of the women participating in the study was 46.59 +/- 11.15 years; 81.5% were married, 57.6% had no knowledge about cervical cancer, and 62.2% had no knowledge about the HPV vaccine, a protective vaccine against cervical cancer. The average scores for the subdimensions of severity, barriers, benefits, and susceptibility of the HBMS-HPVV were 3.19 +/- 0.60, 2.96 +/- 1.22, 2.29 +/- 1.40, and 3.92 +/- 0.49, respectively. The average scores for the subdimensions of personal barriers, social norms, confidence, and worries of the HTABS were 31.14 +/- 19.27, 7.57 +/- 4.47, 30.03 +/- 7.18, and 11.91 +/- 2.52, respectively. A statistically significant positive relationship was found between all HBMS-HPVV subdimensions and the HTABS subdimensions (p < 0.001). Conclusion: The study found that as the perceived severity increases, the perceived benefits, susceptibility, and confidence increase, while the perceived barriers, personal barriers, social norms, and worries decrease. Based on these results, it is recommended that women's health nurses provide education and seminars to raise awareness about cervical cancer, early screening and diagnosis programs, and the HPV vaccine.
Keywords: Attitude; Belief; Hpv Testing; Hpv Vaccine; Knowledge